2021
DOI: 10.1186/s12909-021-02974-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported knowledge, attitudes, practices and barriers in use of evidence-based medicine among resident physicians in Kenya: a mixed methods study

Abstract: Background Evidence based medicine (EBM) helps clinicians to integrate latest research evidence into their daily clinical practice. There is a need for all healthcare professions to adopt it in order to provide safe and most cost-effective care. Postgraduate doctors are at the frontline of healthcare delivery and all medical institutions should strive to produce practitioners of EBM. Studies have shown that physicians are still struggling to adapt to this paradigm shift in the practice of medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…Such results are consistent with the low levels of knowledge and attitude shown by the participants. Similar results shown by many studies conducted in other regions [ 26 ]. The limited practice of EBM could be the result of a range of obstacles such as a lack of time, a lack of sources published in the native language and insufficient skills required in evidence-based practice [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Such results are consistent with the low levels of knowledge and attitude shown by the participants. Similar results shown by many studies conducted in other regions [ 26 ]. The limited practice of EBM could be the result of a range of obstacles such as a lack of time, a lack of sources published in the native language and insufficient skills required in evidence-based practice [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…In Germany and the UK, scarce opportunities for acquiring basic research skills during undergraduate education have been reported 54. Our findings are consistent with observations from Europe, Africa, the Middle East and Latin America 48 55–58. In a survey of Latin American medical students, 67.4% reported not receiving adequate training in research and publication 58.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are consistent with a recent cross-sectional survey conducted in Croatia by Nejašmić D et al They explored that less than half of the family physicians considered the major EBM database (Medline—49.1% and Cochrane library—47.1%) useful for patient care [ 23 ]. Interestingly Unadkat, M.B et al 2021 reported a good understanding of EBM among their study respondents [ 24 ]. These striking dissimilarities were perhaps the result of the diversity of the responding doctors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, EBM-related knowledge was significantly higher among doctors who received formal training for EBM [ 19 ]. A study conducted in Kenya by Unadkat et al reported that age is not a significant factor related to EBM knowledge [ 24 ]. The possible dissimilarities between the current study and this study could be the inclusion criteria of physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation